TOC adsorption material and preparation method thereof
By preparing TOC adsorption materials loaded with molybdenum zirconium resin, the problem of unsatisfactory TOC removal rate in lithium battery recycling liquid is solved, efficient adsorption and purity improvement are achieved, and environmentally friendly and sustainable solutions are provided for lithium battery recycling.
Patent Information
- Application Number
- CN202410254125.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-03-06
AI Technical Summary
The TOC removal rate in the existing lithium battery recycling liquid is not ideal, which affects the purity of the recycling liquid and the corrosion and wear of the equipment.
Using a preparation method of TOC adsorption material, it is swelled by mixing macroporous resin and solvent, add molybdate and enter the pores of the resin, and then adjust the pH value and add zirconium salt to generate ZrO2/Zr(MoO4) 2. Form a molybdenum-laden zirconium resin liquid, and finally collect the solid to prepare a TOC adsorption material.
It realizes efficient adsorption of TOC, improves the purity and quality of lithium battery recycling liquid, reduces corrosion and wear on the equipment, and provides a more sustainable and environmentally friendly solution for lithium battery recycling and reuse.
Smart Images

Figure CN118002090B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adsorption materials, and in particular to a TOC adsorption material and a preparation method thereof. Background Art
[0002] In commercial lithium-ion batteries, organic carbonate electrolyte solvents have always occupied the mainstream position due to their excellent positive electrode interface stability. Ester solvents include cyclic carbonates and linear carbonates. For example, ethylene carbonate (EC) and propylene carbonate (PC) are typical cyclic carbonate solvents. EC has become a necessary component in most electrolytes due to its high dielectric constant, but its high melting point still limits its use alone. Dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are typical representatives of linear carbonates. The new electrolyte formulation based on the mixture of EC and linear carbonate has excellent performance and quickly became the mainstream electrolyte formulation. In addition, new electrolyte solvents such as fluorinated carbonate solvents, sulfone solvents, nitrile solvents, phosphorus solvents, ether solvents and silicon solvents have also been widely studied. Since these electrolytes are organic, organic carbon substances will be produced in the waste liquid recycled during battery recycling, and inorganic carbon will be produced in the positive and negative electrode materials of lithium batteries. These carbon substances are not desirable to be present during recycling.
[0003] Therefore, the technology of removing total organic carbon (TOC) from lithium battery recycling liquid came into being. In the current technology, the more mature methods of removing TOC from lithium solution include membrane separation, extraction separation, continuous ion exchange, adsorption separation and other methods. In particular, the adsorption method has attracted much attention due to its advantages such as low cost and easy operation. However, the current TOC removal resin has the problem of unsatisfactory TOC removal rate. Summary of the invention
[0004] Based on this, the first aspect of the present application provides a method for preparing a TOC adsorption material, and its technical solution is as follows:
[0005] A method for preparing a TOC adsorption material comprises the following steps:
[0006] mixing a macroporous resin and a solvent to swell the macroporous resin to obtain a swollen resin solution;
[0007] Mixing the swollen resin liquid and molybdate so that at least a portion of the molybdate enters the pores of the swollen macroporous resin to obtain a loaded molybdenum resin liquid;
[0008] Adjusting the pH value of the molybdenum-loaded resin liquid to a pH value of less than 7, adding a zirconium salt, so that at least a portion of the zirconium salt enters the pores of the swollen macroporous resin, and reacts with the molybdate in the pores to generate ZrO2 / Zr(MoO4)2, thereby obtaining a molybdenum-loaded zirconium resin liquid;
[0009] The solid in the molybdenum-zirconium loaded resin solution is collected to prepare the TOC adsorption material.
[0010] A second aspect of the present application provides a TOC adsorption material, which is prepared by the preparation method as described above.
[0011] This application has the following beneficial effects:
[0012] 1) The TOC adsorption material prepared in the present application has excellent TOC adsorption performance and high TOC removal rate, and can be used to remove TOC in lithium recovery liquid, which is beneficial to improve the purity and quality of the recovery liquid, reduce corrosion and wear on equipment, and provide a more sustainable and environmentally friendly solution for lithium battery recycling and reuse, making an important contribution to the realization of circular economy and efficient utilization of resources.
[0013] 2) The synthesis of the TOC adsorption material of the present application is green and environmentally friendly. No toxic or harmful gases are generated during the synthesis, thereby reducing the use of toxic reagents and dangerous surface treatment methods.
[0014] 3) The synthesis operation of the TOC adsorption material of the present application is simple. The material prepared by the precipitation method has a smaller particle size and higher activity. The reagent cost is low and the reaction conditions are mild. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0016] Figure 1 This is a physical picture of the TOC adsorption material prepared in Example 1;
[0017] Figure 2 is the XRD pattern of the TOC adsorbent material prepared in Example 1;
[0018] Figure 3 This is a TEM image of the TOC adsorbent material prepared in Example 1. DETAILED DESCRIPTION
[0019] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0021] the term
[0022] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0023] In the present application, the selection range involving "and / or", "or / and", and "and / or" includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the said any and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").
[0024] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0025] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0026] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0027] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0028] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0029] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.
[0030] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0031] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.
[0032] In a first aspect, the present application provides a method for preparing a TOC adsorbent material. In some embodiments, the method for preparing a TOC adsorbent material comprises the following steps:
[0033] S10, mixing a macroporous resin and a solvent to swell the macroporous resin to obtain a swollen resin solution.
[0034] Optionally, the macroporous resin is an anionic macroporous resin. The oxygen bound to the carbon double bond on the TOC molecule produces a carboxylic acid functional group, which is negatively charged. This negative charge allows TOC to exchange with another anion or charge with lower selectivity on the macroporous anion resin, so it is relatively stable.
[0035] Optionally, the macroporous resin is weakly alkaline;
[0036] Optionally, the porosity of the macroporous resin is 60% to 70%;
[0037] Optionally, the pore size of the macroporous resin is 10 nm to 1000 nm;
[0038] Optionally, the macroporous resin includes a tertiary amine group;
[0039] Optionally, the solvent is selected from one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and dimethylacetamide (DMAc).
[0040] The macroporous resin can be swollen in the solvent by magnetic stirring.
[0041] Optionally, the conditions for swelling the macroporous resin include: the ambient temperature is 40-60° C. Preferably, the ambient temperature is 40-50° C.
[0042] Optionally, the conditions for swelling the macroporous resin include: stirring for 4 hours to 8 hours. Preferably, stirring for 6 hours to 7 hours.
[0043] S20, mixing the swollen resin liquid and molybdate, so that at least a portion of the molybdate enters the pores of the swollen macroporous resin, to obtain a loaded molybdenum resin liquid.
[0044] Optionally, the molybdate is selected from one or more of sodium molybdate, potassium molybdate and cobalt molybdate.
[0045] Optionally, the mass ratio of the molybdate to the macroporous resin is (2-2.3): (1-1.5). Preferably, the mass ratio of the molybdate to the macroporous resin is (2-2.3): (1-1.5).
[0046] S30, adjusting the pH value of the molybdenum-loaded resin liquid to a pH value of less than 7, adding a zirconium salt, so that at least part of the zirconium salt enters the pores of the swollen macroporous resin, and reacts with the molybdate in the pores to generate ZrO2 / Zr(MoO4)2, thereby obtaining a molybdenum-loaded zirconium resin liquid.
[0047] Optionally, the pH value of the loaded molybdenum resin solution is adjusted to a pH value of 5-6.
[0048] Optionally, adjusting the pH value of the loaded molybdenum resin solution comprises the following steps: adding oxalic acid to the loaded molybdenum resin solution.
[0049] Optionally, the zirconium salt is selected from one or more of zirconium sulfate, zirconium oxychloride and zirconium nitrate.
[0050] Optionally, the molar ratio of the zirconium element in the zirconium salt to the molybdenum element in the molybdate is (1-1.3): (2-2.5). Preferably, the molar ratio of the zirconium element in the zirconium salt to the molybdenum element in the molybdate is (1-1.1): (2-2.2).
[0051] The zirconium salt and the molybdate can be reacted to generate ZrO2 / Zr(MoO4)2 by a method of heating and refluxing.
[0052] Optionally, the conditions for the zirconium salt and the molybdate to react to generate ZrO2 / Zr(MoO4)2 include: the ambient temperature is 120-140°C. Preferably, the ambient temperature is 120-130°C.
[0053] Optionally, the conditions for the reaction of the zirconium salt and the molybdate to generate ZrO2 / Zr(MoO4)2 include: reflux for 6h to 9h. Preferably, reflux for 7h to 8h.
[0054] S40, collecting the solid in the molybdenum-zirconium loaded resin liquid to prepare the TOC adsorption material.
[0055] Optionally, the loaded molybdenum-zirconium resin solution can be filtered, and the solid can be collected, washed and dried to obtain a TOC adsorption material.
[0056] Optionally, the washing reagent includes water and ethanol, wherein the water may be deionized water, and optionally, the drying method may be drying.
[0057] The TOC adsorption material prepared in the above embodiment has excellent TOC adsorption performance and high TOC removal rate, and can be used to remove TOC in lithium recovery liquid, which is beneficial to improve the purity and quality of the recovery liquid, reduce corrosion and wear on equipment, and provide a more sustainable and environmentally friendly solution for lithium battery recycling and reuse, making an important contribution to the realization of circular economy and efficient utilization of resources.
[0058] The synthesis of the TOC adsorption material of the above embodiment is green and environmentally friendly, no toxic or harmful gas is generated during the synthesis, and the use of toxic reagents and dangerous surface treatment methods is reduced.
[0059] The TOC adsorption material of the above embodiment is simple to synthesize. The TOC adsorption material prepared by the precipitation method has an average particle size of 5 μm to 20 μm, a small particle size, higher activity, low reagent cost, and mild reaction conditions.
[0060] The second aspect of the present application provides a TOC adsorption material, which is prepared by the preparation method described above. In some embodiments, the average particle size of the TOC adsorption material is 5 μm to 20 μm.
[0061] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.
[0062] The anionic macroporous resin model is D301.
[0063] Example 1
[0064] This embodiment provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0065] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 50 °C and stirred for 6 h to obtain a swollen resin solution;
[0066] (b) Adding molybdate: adding sodium molybdate to the swollen resin solution of (a) at a mass ratio of molybdate to anionic macroporous resin of 2:1, and stirring magnetically at room temperature until mixed to obtain a loaded molybdenum resin solution;
[0067] (c) Adjusting pH: adding oxalic acid to the molybdenum-loaded resin solution of (b) to adjust the pH to 5-6;
[0068] (d) Adding zirconium salt: adding zirconium oxychloride to the molybdenum loaded resin solution of pH 5 to 6 in (c) according to the molar ratio of zirconium element in zirconium salt to molybdenum element in molybdate of 1:2, heating to 120° C. and reacting for 8 h to obtain molybdenum loaded zirconium resin solution;
[0069] (e) Purification: Filter the loaded molybdenum zirconium resin solution in step (d), collect the solid, wash and dry it to obtain a TOC adsorption material, which is referred to as product A.
[0070] The physical picture of product A is as follows Figure 1 As shown. XRD characterization of product A is performed, and the results are shown in Figure 2 ,Depend on Figure 2 It can be seen that product A is ZrO2 / Zr(MoO4)2, which is composed of two substances: ZrO2 and Zr(MoO4)2. TEM characterization of product A is shown in Figure 3 .
[0071] Example 2
[0072] This embodiment provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0073] (a) Swelling: 330 g of anionic macroporous resin and 300 mL of DMF were stirred and mixed, and then heated to 50 °C and stirred for 6 h to obtain a swollen resin solution;
[0074] (b) Adding molybdate: adding sodium molybdate to the swollen resin solution of (a) at a mass ratio of molybdate to anionic macroporous resin of 2:1.2, and stirring magnetically at room temperature until mixed to obtain a loaded molybdenum resin solution;
[0075] (c) Adjusting pH: adding oxalic acid to the molybdenum-loaded resin solution of (b) to adjust the pH to 5-6;
[0076] (d) Adding zirconium salt: adding zirconium oxychloride to the molybdenum loaded resin solution of pH 5 to 6 in (c) according to the molar ratio of zirconium element in zirconium salt to molybdenum element in molybdate of 1:2, heating to 120° C. and reacting for 8 h to obtain molybdenum loaded zirconium resin solution;
[0077] (e) Purification: Filter the loaded molybdenum-zirconium resin solution in step (d), collect the solid, wash and dry it to obtain a TOC adsorption material, which is referred to as product B.
[0078] Example 3
[0079] This embodiment provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0080] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 30 °C and stirred for 6 h to obtain a swollen resin solution;
[0081] (b) Adding molybdate: Sodium molybdate is dissolved in the swollen resin solution of (a) at a mass ratio of molybdate to anionic macroporous resin of 2:1, and magnetic stirring is performed at room temperature until the mixture is uniform, thereby obtaining a loaded molybdenum resin solution;
[0082] (c) Adjusting pH: adding oxalic acid to the molybdenum-loaded resin solution of (b) to adjust the pH to 5-6;
[0083] (d) Adding zirconium salt: adding zirconium oxychloride to the loaded molybdenum resin solution of pH 5 to 6 in (c) according to the molar ratio of zirconium element in zirconium salt to molybdenum element in molybdate of 1:2.2, heating to 120° C. and reacting for 8 h to obtain a loaded molybdenum zirconium resin solution;
[0084] (e) Purification: Filter the loaded molybdenum-zirconium resin solution in step (d), collect the solid, wash and dry it to obtain a TOC adsorption material, which is recorded as product C.
[0085] Example 4
[0086] This embodiment provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0087] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 30 °C and stirred for 6 h to obtain a swollen resin solution;
[0088] (b) Adding molybdate: Sodium molybdate is dissolved in the swollen resin solution of (a) at a mass ratio of molybdate to anionic macroporous resin of 2:1, and magnetic stirring is performed at room temperature until the mixture is uniform, thereby obtaining a loaded molybdenum resin solution;
[0089] (c) Adjusting pH: adding oxalic acid to the molybdenum-loaded resin solution of (b) to adjust the pH to 5-6;
[0090] (d) Adding zirconium salt: according to the molar ratio of zirconium element in zirconium salt to molybdenum element in molybdate of 1:2.2, zirconium oxychloride is added to the loaded molybdenum resin solution of pH 5-6 in (c), and the temperature is raised to 120° C. to react for 6 hours to obtain the loaded molybdenum zirconium resin solution.
[0091] (e) Purification: Filter the loaded molybdenum-zirconium resin solution in step (d), collect the solid, wash and dry it to obtain a TOC adsorption material, which is recorded as product D.
[0092] Comparative Example 1
[0093] This comparative example provides a commercially available TOC adsorption material, model D4020, recorded as product E.
[0094] Comparative Example 2
[0095] This comparative example provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0096] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 50 °C and stirred for 6 h to obtain a swollen resin solution;
[0097] (b) Adding zirconium salt: adding zirconium oxychloride to the swollen resin solution of (a) at a mass ratio of zirconium salt to anionic macroporous resin of 1:1, and stirring magnetically at room temperature until mixed to obtain a loaded zirconium resin solution;
[0098] (c) Purification: Filter the loaded zirconium resin solution in step (b), collect the solid, wash and dry it to obtain a TOC adsorption material, which is referred to as product F.
[0099] Comparative Example 3
[0100] This comparative example provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0101] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 50 °C and stirred for 6 h to obtain a swollen resin solution;
[0102] (b) Adding zirconium salt: adding zirconium oxychloride to the swollen resin solution of (a) at a mass ratio of zirconium salt to anionic macroporous resin of 1:1, then adding sodium hydroxide aqueous solution, adjusting the pH to 8-9, and magnetically stirring at room temperature until mixed, to obtain a loaded zirconium resin solution;
[0103] (c) Purification: Filter the loaded zirconium resin solution in step (b), collect the solid, wash and dry it to obtain a TOC adsorption material, which is referred to as product G.
[0104] Comparative Example 4
[0105] This comparative example provides a TOC adsorption material and a preparation method thereof, the steps are as follows:
[0106] (a) Swelling: 200 g of anionic macroporous resin was mixed with 300 mL of DMF, and then heated to 50 °C and stirred for 6 h to obtain a swollen resin solution;
[0107] (b) Adding zirconium salt: adding zirconium oxychloride to the swollen resin solution of (a) at a mass ratio of zirconium salt to anionic macroporous resin of 1:1, and stirring magnetically at room temperature until mixed to obtain a loaded zirconium resin solution;
[0108] (c) Adjusting pH: adding oxalic acid to the molybdenum-loaded resin solution of (b) to adjust the pH to 5-6;
[0109] (d) Adding molybdate: according to the molar ratio of molybdenum element in molybdate to zirconium element in zirconium salt of 2:1, sodium molybdate is added to the loaded molybdenum resin solution of pH 5-6 in (c), and the temperature is raised to 120° C. for reaction for 8 hours to obtain a loaded molybdenum-zirconium resin solution;
[0110] (e) Purification: Filter the loaded molybdenum zirconium resin solution in step (d), collect the solid, wash and dry it to obtain a TOC adsorption material, which is recorded as product H.
[0111] Test 1:
[0112] The following performance tests were performed on the products A to G obtained in each embodiment and comparative example:
[0113] (1) Take raw water with a pH of 2 to 3 for lithium battery recovery liquid, test the TOC content in the raw water, and the results are shown in Table 1. Divide it into 8 portions, each of which is 100 mL. (2) Take 10 mL of products A to G prepared in each embodiment and comparative example, and add them to 8 portions of raw water respectively; (3) The liquid in step (2) is placed in a 250 mL conical flask, oscillated in a constant temperature oscillator for 12 h, and passed through a 0.45 micron membrane to measure the TOC content in the liquid after adsorption treatment. The results are shown in Table 1.
[0114] Table 1
[0115]
[0116] It can be seen from Table 1 that products A~D can efficiently adsorb TOC and have high TOC removal rates.
[0117] Test 2:
[0118] The following performance tests were performed on the products A, E~G obtained in Example 1 and the comparative examples:
[0119] (1) Take 10 mL of each of the products A, E~G prepared in Example 1 and Comparative Examples 1~4 and load them into the resin column respectively. (2) Take the raw water of lithium battery recovery liquid and divide it into 5 parts. (3) Make each part of the raw water flow through the resin column containing products A, E~G respectively. The adsorption flow rate is shown in Table 2. The TOC content in the outflowing liquid is measured. The results are shown in Table 2.
[0120] Table 2
[0121]
[0122] As can be seen from Table 2, product A maintains good adsorption performance at a flow rate of 10 BV / h.
[0123] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0124] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a total organic carbon adsorption material in lithium battery recovery liquid, characterized in that: The following steps are involved: mixing a macroporous resin and a solvent to swell the macroporous resin to obtain a swollen resin solution; Mixing the swollen resin liquid and sodium molybdate so that at least a portion of the sodium molybdate enters the pores of the swollen macroporous resin to obtain a loaded molybdenum resin liquid; The pH value of the loaded molybdenum resin liquid is adjusted to a pH value of less than 7, and zirconium oxychloride is added, so that at least a portion of the zirconium oxychloride enters the pores of the swollen macroporous resin and reacts with sodium molybdate in the pores to generate ZrO2 / Zr(MoO4)2, thereby obtaining a loaded molybdenum zirconium resin liquid; wherein the conditions for the reaction of the zirconium oxychloride with the sodium molybdate to generate ZrO2 / Zr(MoO4)2 include: an ambient temperature of 120 to 140°C and reflux for 6 to 9 hours; The solid in the molybdenum-zirconium loaded resin solution is collected to prepare a TOC adsorption material.
2. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to claim 1, characterized in that: The conditions for the zirconium oxychloride to react with the sodium molybdate to generate ZrO2 / Zr(MoO4)2 include: the ambient temperature is 120-130°C.
3. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to claim 1, characterized in that: The conditions for the zirconium oxychloride to react with the sodium molybdate to generate ZrO2 / Zr(MoO4)2 include: reflux for 7h to 8h.
4. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to claim 1, characterized in that: The pH value of the loaded molybdenum resin solution is adjusted to a pH value of 5 to 6.
5. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to claim 4, characterized in that: Regulating the pH value of the loaded platinum resin solution comprises the following steps: Add oxalic acid to the loaded molybdenum resin solution.
6. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to any one of claims 1 to 5, characterized in that: The mass ratio of the sodium molybdate to the macroporous resin is (2-2.3):(1-1.5).
7. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to any one of claims 1 to 5, characterized in that: The molar ratio of the zirconium element in the zirconium oxychloride to the molybdenum element in the sodium molybdate is (1-1.3):(2-2.5).
8. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to any one of claims 1 to 5, characterized in that: Includes at least one of the following features: (1) The macroporous resin is an anionic macroporous resin; (2) the macroporous resin is weakly alkaline; (3) The porosity of the macroporous resin is 60% to 70%; (4) The pore size of the macroporous resin is 10 nm to 1000 nm; (5) the macroporous resin includes a tertiary amine group; (6) The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide and dimethylacetamide.
9. The method for preparing the total organic carbon adsorption material in lithium battery recovery liquid according to any one of claims 1 to 5, characterized in that: The conditions for swelling the macroporous resin include at least one of the following conditions: (1) The ambient temperature is 40-60°C; (2) Stir for 4 to 8 hours.
10. A total organic carbon adsorption material in lithium battery recovery liquid, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
11. The total organic carbon adsorption material in lithium battery recovery liquid according to claim 10, characterized in that: The average particle size of the total organic carbon adsorption material in the lithium battery recovery liquid is 5 μm to 20 μm.
Citation Information
Patent Citations
Nano molybdate resin-supported resin composite adsorbent, and preparation method and application thereof
CN110215913A